PENGARUH PENGEMBANGAN KARIR KARYAWAN TETAP TERHADAP KEPUASAN KINERJA KARYAWAN ROCKY PLAZA HOTEL PADANG - Winda Diana; Vina Kumala; Trio Averia Lesmana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research was motivated by the discovery of problems related to career development and employee job satisfaction at Rocky Plaza Hotel Padang, the purpose of this study was to determine the effect of career development on employee job satisfaction at Rocky Plaza Hotel Padang. This research is a quantitative descriptive study with a causal associative approach. . The population in this study were all employees of Rocky Plaza Hotel Padang except for the Head of Department (HOD) which amounted to 150 employees. The number of samples in this study was 60 people. The sampling technique in this study used simple random sampling. Data collection techniques were carried out using a questionnaire (questionnaire) using a Likert scale that had been tested for validity and reliability. Data analysis technique using SPSS version 16.0 program. The results of this study indicate that; 1) career development Rocky Plaza Hotel Padang as many as 13.3% of respondents said it was good and 86.7% said it was not good. 2) Job satisfaction of Rocky Plaza Hotel Padang employees as many as 21.7% of respondents said they were satisfied and 78.3% said they were not satisfied. 3) there is a significant effect between career development and employee job satisfaction at Rocky Plaza Hotel Padang, with a regression coefficient of 8.526 in sig. 0.00 < 0.05. This means that every increase of 1 unit of career development will increase employee job satisfaction by 8,526 units. While the magnitude of the influence of career development on employee job satisfaction Rocky Plaza Hotel Padang is 55.6%, while the rest is influenced by other factors